A Controversy Over the Existence of Fictional Objects: Husserl and Ingarden on Imagination and Fiction. Issue 51 (2nd January 2020) - Płotka, Witold
ABSTRACT: This paper explores the structure and elements of the intentional experiences of imagining fictional objects. The author critically examines the argument that whereas Husserl's theory of imagination cannot do justice to fictional objects, Ingarden's theory of purely intentional objects provides a basis for the theory of intentionality that explains the status of fictional objects. The paper discusses this argument to show that it is justified only in regard to Husserl's early account of imagination, and on the condition of understanding contents as the phantasmas. Moreover, the author sketches Ingarden's theory of imagination, and compares it to Husserl's later account of imagination in terms of noetic-noematic structures. Finally, the author questions the sharp distinction between Husserl and Ingarden with respect to their theories of imagination and fictional objects by showing that it is hard to classify clearly their theories as content or object theories respectively.